2016
DOI: 10.7554/elife.15034
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and stochastic growth regulation of biliary epithelial cells dictate dynamic epithelial tissue remodeling

Abstract: Dynamic remodeling of the intrahepatic biliary epithelial tissue plays key roles in liver regeneration, yet the cellular basis for this process remains unclear. We took an unbiased approach based on in vivo clonal labeling and tracking of biliary epithelial cells in the three-dimensional landscape, in combination with mathematical simulation, to understand their mode of proliferation in a mouse liver injury model where the nascent biliary structure formed in a tissue-intrinsic manner. An apparent heterogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
106
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 44 publications
4
106
3
Order By: Relevance
“…Our data indicate that the phenotypic impact arises predominantly downstream of the biliary injury in this model. Ductular reactions, the hallmark pathologic finding typical of cholestatic liver injury, arise from prominin‐1 ‐expressing hepatic progenitor cells within the portal triads of the hepatic lobule . Using a thioacetamide‐induced chronic liver injury, Kamimoto et al demonstrated that although the majority of intrahepatic biliary epithelial cells undergo a limited number of cell divisions during biliary tree remodeling, a small subset of Prom1 ‐expressing progenitor cells maintain proliferative capacity and continually generate new biliary epithelial cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data indicate that the phenotypic impact arises predominantly downstream of the biliary injury in this model. Ductular reactions, the hallmark pathologic finding typical of cholestatic liver injury, arise from prominin‐1 ‐expressing hepatic progenitor cells within the portal triads of the hepatic lobule . Using a thioacetamide‐induced chronic liver injury, Kamimoto et al demonstrated that although the majority of intrahepatic biliary epithelial cells undergo a limited number of cell divisions during biliary tree remodeling, a small subset of Prom1 ‐expressing progenitor cells maintain proliferative capacity and continually generate new biliary epithelial cells .…”
Section: Discussionmentioning
confidence: 99%
“…Cultured Prom1 ‐expressing HPCs, clonally expanded from Mat1a null mice treated with the hepatotoxin 3,5‐diethoxycarbonyl‐1,4‐dihydrocollidine (DDC), undergo myofibroblastic differentiation and express Collagen‐1α1 when treated with pro‐fibrogenic transforming growth factor β (TGF‐β). Recent cell lineage tracing analyses indicate that biliary cells involved in ductular reactions derive from Prom1 ‐expressing progenitor cells in association with cholestatic injury …”
mentioning
confidence: 99%
“…On the other hand, frequently used markers to identify DRCs, such as epithelial cell adhesion molecule, SOX9, and cytokeratins 7 and 19, lack specificity as they are not exclusively expressed by DRCs but also by normal cholangiocytes and, in some cases, SCs. Nevertheless, recent lineage‐tracing studies have demonstrated that DRCs in biliary injury are mainly derived from the expansion of proliferative cholangiocytes (particularly of a select population with persistent proliferative activity) and/or activation of biliary tree progenitor/stem cells in the peribiliary gland niche . This etiology‐dependent origin of DRCs likely affects their interaction with nonparenchymal cells within the ductular reaction, as demonstrated by a recent study that compared the transcriptomic profile of DRCs/HPCs from hepatitis C virus–infected and PSC livers as models for hepatocellular or biliary injury, respectively.…”
Section: The Proliferative Cholangiocyte Compartment In Psc: Drcsmentioning
confidence: 99%
“…Nevertheless, recent lineage-tracing studies have demonstrated that DRCs in biliary injury are mainly derived from the expansion of proliferative cholangiocytes (particularly of a select population with persistent proliferative activity) and/or activation of biliary tree progenitor/ stem cells in the peribiliary gland niche. (13,16,17) This etiology-dependent origin of DRCs likely affects their interaction with nonparenchymal cells within the ductular reaction, as demonstrated by a recent study that compared the transcriptomic profile of DRCs/HPCs from hepatitis C virus-infected and PSC livers as models for hepatocellular or biliary injury, respectively. The study identified significant differences in the expression of over 300 genes between the DRCs of the two diseases and defined how these differences influence the recruiting and homing of inflammatory cells.…”
Section: The Proliferative Cholangiocyte Compartment In Psc: Drcsmentioning
confidence: 99%
“…In the zebrafish liver most BECs directly contact surrounding hepatocytes, whereas in the mammalian liver only BECs that reside in intrahepatic bile ductules directly contact hepatocytes. Although in the healthy mouse liver BECs in bile ductules are a small portion of the total BECs, in the injured liver bile ductules elongate through the proliferation of BECs, making longer and denser bile ductules . These extended ductules appear to replace collapsed bile canaliculi between damaged hepatocytes, thereby restoring bile drain.…”
Section: Discussionmentioning
confidence: 99%